MORE FLORET1 Interacts with C-type Replication Protein A Complex and Regulates Male Meiosis in Rice - Lianjun Zhu; Rou Chen; Yu Huang; Guobin Liang; Jinwen Wu; Haibin Guo; Xiangdong Liu; Zijun Lu (Rice)
Abstract Meiosis plays a pivotal role in plant reproduction, which is also crucial for enhancing genetic diversity. Although the impact of MOF1 on floral organ development and its negative regulation of the key tapetal gene PKS2 have been established, the specific function of MOF1 in male meiotic process remains elusive. In this study, we identified two mutant lines of MOF1 in Nipponbare background. Compared to the wild-type controls, MOF1 mutations resulted in significant reductions in seed setting rate and pollen fertility, partially attributed to its defects in the formation of male meiotic bivalents. RNA-seq analyses and RT-qPCR assays revealed that loss-of-function mutation of MOF1 didn’t alter expression levels of 60 known meiotic-regulated genes, suggesting that MOF1 may not function as a transcriptional factor in its meiotic regulation. Yeast two-hybrid and bimolecular fluorescence complementation assays demonstrated the protein-protein interactions among MOF1, RPA2c, RPA1c, as well as FAR1, among which RPA1c and RPA2c involved in meiotic bivalent formation. Furthermore, gene expression pattern analyses and subcellular localization studies indicated the co-expression among above interacted proteins in nucleus during anther development. Our findings provide a mechanistic insight into how MOF1 modulate male meiosis possibly through interactions with key meiotic proteins, facilitating a better understanding of male reproductive regulation.